Human Face Perception Using Electroencephalography and Magnetoencephalography - Miki, Kensaku; Takeshima, Yasuyuki; Watanabe, Shoko; Kakigi, Ryusuke (Frontiers in Physiology, 2022)
The face has a large amount of information that is useful for humans in social communication. Recently, non-invasive methods have been used to investigate human brain activity related to perception and cognition processes. Electroencephalography (EEG) and magnetoencephalography (MEG) have excellent temporal resolution and reasonably good spatial resolution. Therefore, they are useful to investigate time sequences of human brain activity related to the face perception process. In this review, we introduce our previous EEG and MEG studies of human face perception that demonstrated the following characteristics of face perception processing: (1) Event-related components in the temporal area related to the activity in the inferior temporal (IT) area, corresponding to the fusiform face area, are evoked approximately 180 msec after the presentation of a face. The activity in the IT area plays an important role in the detection processing of a face, and the contours of a face affect the activity in the IT areas. (2) Event-related components in the temporal area related to the superior temporal sulcus activity are larger when eyes are averted than when directly looking into the eyes. (3) The direction of features of a face affects the face perception processing in the right hemisphere. On the other hand, the matching of the direction between the contours and features of a face affects the processing in the left hemisphere. (4) Random dots blinking, which uses temporal changes in patterns of many small dots to present stimuli without a change in luminance during the presentation of a face, is a useful visual stimulus method to investigate the brain activity related to face perception processing in the IT area using EEG and MEG.